A companion to Hong Kong cinema - Cheung, Esther M. K.; Marchetti, Gina; Yau, Ching-Mei Esther (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2015)
A Companion to Hong Kong Cinema provides the first comprehensive scholarly exploration of this unique global cinema. By embracing the interdisciplinary approach of contemporary film and cultural studies, this collection navigates theoretical debates while charting a new course for future research in Hong Kong film. -Examines Hong Kong cinema within an interdisciplinary context, drawing connections between media, gender, and Asian studies, Asian regional studies, Chinese language and cultural studies, global studies, and critical theory -Highlights the often contentious debates that shape current thinking about film as a medium and its possible future -Investigates how changing research on gender, the body, and sexual orientation alter the ways in which we analyze sexual difference in Hong Kong cinema -Charts how developments in theories of colonialism, postcolonialism, globalization, neoliberalism, Orientalism, and nationalism transform our understanding of the economics and politics of the Hong Kong film industry -Explores how the concepts of diaspora, nostalgia, exile, and trauma offer opportunities to rethink accepted ways of understanding Hong Kong's popular cinematic genres and stars.
Introduction / Esther M.K. Cheung, Gina Marchetti & Esther C. M. Yau -- Section A: Critical paradigms: defining Hong Kong cinema studies. Watchful partners, hidden currents: Hong Kong cinema moving into the mainland of China / Esther C.M. Yau -- The urban maze: crisis and topography in Hong Kong cinema / Esther M.K. Cheung -- Hong Kong cinema as ethnic borderland / Kwai-Cheung Lo -- Hong Kong cinema in the age of neoliberalization and mainlandization: Hong Kong SAR new wave as a cinema of anxiety / Mirana May Szeto & Yun-Chung Chen -- Commentary: dimensions of Hong Kong cinema / Sheldon Lu -- Section B: Critical geographies. Hong Kong cinema's exotic others: re-examining the Hong Kong body in the context of Asian regionalism / Olivia Khoo -- Animating the translocal: the Mcdull films as a cultural and visual expression of Hong Kong / Kimburley Wing-Yee Choi & Steve Fore -- Globalizing Hong Kong cinema through Japan / David Desser -- Creative cinematic geographies through the Hong Kong international film festival / Cindy Hing-Yuk Wong -- Postmodernity, Han normativity and Hong Kong cinema / Evans Chan -- Commentary: critical geographies / Stephen Yiu-Wai Chu -- The gendered body and queer configurations. Feminism, post-feminism, and Hong Kong women filmmakers / Gina Marchetti -- Love in the city: the placing of intimacy in urban romance films / Helen Hok-Sze Leung -- Regulating queer domesticity in the neoliberal diaspora / Audrey Yue -- Commentary: to love is to demand: a very short commentary / Shu-Mei Shih -- Hong Kong stars. Return of the dragon: handover, Hong Kong cinema, and Chinese ethno-nationalism / Paul Bowman -- Transitional stardom: the case of Jimmy Wang Yu / Tony Williams -- Camp stars of androgyny: a study of Leslie Cheung and Anita Mui's body images of desire / Natalia Siu-Hung Chan -- Cooling Faye Wong: a cosmopolitical intervention / Kin-Yan Szeto -- Commentary: Hong Kong stars and stardom / Gary Bettinson -- Section E: narratives and aesthetics. Making merry on time: a feast of nostalgia in watching Chinese New Year films / Fiona Yuk-Wa Law -- A pan-Asian cinema of allusion: Going home and Dumplings / Bliss Cua Lim -- Double agents, cameos, and the poor man's orchestra: music and place in Chungking Express / Giorgio Biancorosso -- Documenting sentiments in video diaries around 1997: archeology of forgotten screen practices / Linda Chiu-Han Lai -- Commentary: the dynamics of off-centeredness in Hong Kong cinema / Yingjin Zhang -- Section F: screen histories and documentary practices. The lightness of history: screening the past in Hong Kong cinema / Vivian P.Y. Lee -- The tales of Fang Peilin and Zhu Shilin: from rethinking Hong Kong cinema to rewriting Chinese film history / Ain-Ling Wong -- The documentary film in Hong Kong / Ian Aitken & Mike Ingham -- Representations of law in Hong Kong cinema / Marco Wan -- Commentary: cinema and the cultural politics of identity: Hong Kong no more? / Stephen Ching-Kiu Chan.
Includes bibliographical references and index.
Includes filmography.
Description based on print version record and CIP data provided by publisher.
Keywords: Motion pictures -- China -- Hong Kong -- History; Documentary films -- China -- Hong Kong -- History and criticism; Documentary films; Motion pictures; PERFORMING ARTS / Reference; China -- Hong Kong; Criticism, interpretation, etc; History; Electronic books